Second Language Refugee Learners in Egypt: Needs and Challenges - May Soliman (Journal of English Language Teaching and Linguistics, 2023)
The act of leaving one's country, home, friends, and family seeking a haven in another country is a traumatizing process that has a long-lasting impact on humans. Refugees always face a lot of challenges concerning the cultural, psychological, and educational aspects of the countries in which they seek refuge in. The case of refugees in Egypt is rather different from any other country. Egypt is the refuge for many neighboring Arab and African countries experiencing political and civil turmoil. Many of these refugees succeed in blending in Egyptian society, while others keep struggling. This paper aims at understanding the learning goals of refugees from different countries in learning English as a second language though English is not the first language in Egypt. The paper also aims at understanding the different needs of the refugees when learning English as a second language and the challenges they face. In addition, the paper seeks to understand whether the nationality of the teacher differs in the refugees’ perception of success in learning a second language. The paper employs both qualitative and quantitative methods in collecting data from displaced learners of English as a second language and the instructors who teach them to achieve a comprehensive view of the needs and challenges of refugees from different origins, nationalities, and circumstances. The results of the present study indicate that refugees in Egypt mostly learn English for relocation purposes which entails being keen on learning specific language skills more than others. In addition, both the views of the learners and the instructors differ regarding how effective they see the nationality of the instructor in the process of learning a second language. These results should be considered by curriculum developers, instructors, and NGOs to accommodate the refugees’ needs in learning a second language.